A method to estimate climate-critical construction materials applied to seaport protection. (September 2016) - Becker, Austin; Chase, Nathan T.L.; Fischer, Martin; Schwegler, Ben; Mosher, Keith
Highlights: Climate change could result in a worldwide race for adaptation resources. Our method estimates potential global demand for climate construction materials. Our approach leverages local data and engineering designs to estimate global demand. We tested our "minimum assumption credible design" approach for 221 seaports. Less than 10% of seaports require ∼436 M cubic meters of material for 2 m of sea level rise. Abstract: Climate adaptation for coastal infrastructure projects raises unique challenges because global-scale environmental changes may require similar projects to be completed in many locations over the same time frame. Existing methods to forecast resource demand and capacity do not consider this phenomenon of a global change affecting many localities and the resulting increased demand for resources. Current methods do not relate to the most up-to-date climate science information, and they are too costly or too imprecise to generate global, regional, and local forecasts of "climate-critical resources" that will be required for infrastructure protection. They either require too much effort to create the many localized designs or are too coarse to consider information sources about local conditions and structure-specific engineering knowledge. We formalized the concept of a "minimum assumption credible design" (MACD) to leverage available local information (topography/bathymetry and existing infrastructure) and the essential engineering knowledge and required construction materials (i.e., a design cross-section template). The aggregation of the resources required for individual local structures then forecasts the resource demand for global adaptation projects. We illustrate the application of the MACD method to estimate the demand for construction materials critical to protect seaports from sea-level-rise-enhanced storm surges. We examined 221 of the world's 3, 300+ seaports to calculate the resource requirements for a coastal storm surge protection structure suited to current upper-bound projections of two meters of sea level rise by 2100. We found that a project of this scale would require approximately 436 million cubic meters of construction materials, including cement, sand, aggregate, steel rebar, and riprap. For cement alone, ∼49 million metric tons would be required. The deployment of the MACD method would make resource forecasts for adaptation projects more transparent and widely accessible and would highlight areas where current engineering knowledge or material, engineering workforce, and equipment capacity fall short of meeting the demands of adaptation projects.